Eight-day fasting modulates serum kynurenines in healthy men at rest and after exercise - Juhas, Ulana; Reczkowicz, Joanna; Kortas, Jakub Antoni; Żychowska, Małgorzata; Pilis, Karol; Ziemann, Ewa; Cytrych, Inga; Antosiewicz, Jędrzej; Borkowska, Andżelika (Frontiers in Endocrinology, 2024)
Tryptophan’s (Trp) metabolites are undervalued markers of human health. Their serum concentrations are modified by physical exercise and other factors, among which fasting has a well-documented role. Although this mechanism is hardly explored, thus, the study aimed to determine the effect of the 8-day fasting period and the impact of such a procedure on a single bout of an endurance exercise on the concentration of kynurenine pathway (KP) metabolites. 10 participants fasted for 8 days, and 10 as a control group participated in the study. The exercise was performed at baseline after an overnight fast and repeated post 8 days. The 8 days of fasting increased the resting 3-hydroxy-L-kynurenine (3HK), picolinic acid (PA), kynurenic acid (KYNA), and xanthurenic acid (XA) serum concentration. Also elevated phenylalanine (Phe) and tyrosine (Tyr) levels were recorded, suggesting expanded proteolysis of muscle proteins. In turn, physical activity caused a decrease in the concentration of 3-hydroxyanthranilic acid (3HAA) and PA after fasting. The obtained results were not recorded in controls. In conclusion, the results of this study show that the health-promoting effects of fasting are associated with changes in the KYN pathway. The increase in the concentration of PA and XA metabolites following fasting is capable of penetrating the blood-brain barrier, and KYNA, which initiates several beneficial changes, supports this assumption.